Policy simulation for improving self-sufficiency level of beef sub-sector in Malaysia - Buda, Mark (2013)
Beef sub-sector in Malaysia has become significantly important as the demand for beef is increasing every year. However, the pace of development for beef sub-sector is still far to meet the self-sufficiency level. The production of beef sub-sector is far left behind by the production of pork and broiler. Beef sub-sector production has to depend on import of live animal and frozen or chilled beef in order to fill the differences between total demand and local supply of beef. Although the government always emphasizes more on the development of beef sub-sector, the outcomes is yet to be seen. At the same time, it has to improve the development of mutton sub-sector and maintain the development of pork and broiler sub-sectors in order to meet the protein requirement of Malaysian population. Generally, the objective of this study is to simulate policy variables affecting the self-sufficiency level of beef sub-sector. Specifically, this study tries to determine factors affecting the meat production and demand, to simulate the effect of importation of cattle for breeding and cattle for slaughter or feeder cattle on self-sufficiency level of beef sub-sector, and to identify the effect of changes of beef sub-sector on other livestock sub-sectors. In attempts to analyze the objective of this study, econometric modeling procedure is adopted. Structural equations have been developed for each livestock sub-sectors in the industry using general equation of the market model. Each sub-sector model consists of 3 blocks of component which are inventory, supply, and demand. Most of endogenous variables are represented by separate behavioral equations. Other endogenous variables are identities. The exogenous variables, on the other hand, consist of macroeconomic, policy and other exogenous variables. Econometric modeling for this study use annual time series data to estimate each of the subsectors models of the livestock industry. The estimation technique used is 2SLS regression as system of equations. The models are validated through historical simulation using RMSE, RMSPE, and U-Theil inequality coefficient. Then the beef sub-sector policy simulation analysis is conducted based on Malaysian Agricultural Policy Analysis (MAgPA) model framework. Three different scenarios are set by applying different rates of changes of import of cattle for breeding (ICTB) and import of cattle for slaughter or feeder cattle (ICTS) to achieve the current targeted self-sufficiency level of beef sub-sector in Malaysia of 32.7% by 2020 (National Agro-Food Policy). Firstly, in scenario 1, the rates of changes for ICTB and ICTS are 10% and 15% respectively. Other exogenous variables grow based on the growth rates or rates of changes of the last 10 years data. Then scenario 2 examines the sudden increase in ICTB as the rate of changes is 20% while ICTS value remains at the same level. Other exogenous variables grow as in scenario 1. Finally, scenario 3 assumes there is a sudden increase in ICTS as the rate of changes is 20% while ICTB value remains at the same level. Other exogenous variables grow as in scenario 1. The estimation results show the importance of breeding performance in developing the livestock industry. For instance, female cattle in beef sub-sector have the influence on most of the variables in the inventory block. On the demand side, all meat is significantly influence by income with only income elasticity of demand for beef is elastic. Each meat has two substitutes with chicken meat appear to be substitute for all other meat. The beef sub-sector policy simulation analysis found that scenario 2 not only did not achieve the targeted self-sufficiency level for beef sub-sector, but the level is declining. Scenario 2 also records the lowest self-sufficiency level for mutton and chicken meat, and the consumer surplus in beef sub-sector. Scenario 3, though achieve the highest self-sufficiency, producer surplus in beef sub-sector is the lowest. Self-sufficiency level for mutton and pork in scenario 3 are also lower than in scenario 1. Scenario 1 performs the most ideal implication for the beef sub-sector where the targeted beef self-sufficiency level was achieved and other livestock subsectors were stable. Therefore, based on scenario 1, Malaysia should import 68,205 heads of cattle for breeding and 226,841 heads of cattle for slaughter or feeder cattle by year 2017 in order to archive the targeted beef self-sufficiency level in year 2020.